2015
DOI: 10.1136/bmjdrc-2015-000144
|View full text |Cite
|
Sign up to set email alerts
|

Internet-delivered cognitive behaviour therapy for depression in people with diabetes: study protocol for a randomised controlled trial

Abstract: IntroductionDepression substantially contributes to the personal burden and healthcare costs of living with diabetes mellitus (DM). Comorbid depression and DM are associated with poorer quality of life, poorer self-management and glycemic control, increased risk for DM complications and higher mortality rates, and higher health service utilization. Depression remains under-recognized and undertreated in people with DM, which may, in part, result from barriers associated with accessing face-to-face treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Diabetes-specific cognitive behavioral group therapy for people with diabetes and subclinical depression [34] and webbased guided CBT for people with T1DM or T2DM and mild to moderate depression [35] have also reported significant reductions in both depression and diabetes distress. Further trials utilizing Internet and mobile technologies for the mental health of people with diabetes are currently being conducted [36], including our own study using a local iCBT study for depression in people with diabetes [37]. A recent report of an online diabetes self-management program, of the sort which could compliment depression resources reported 'small but significant' benefits as a stand-alone program [38] but points to the need for a mixture of face-to-face and online resources targeted to individual needs.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes-specific cognitive behavioral group therapy for people with diabetes and subclinical depression [34] and webbased guided CBT for people with T1DM or T2DM and mild to moderate depression [35] have also reported significant reductions in both depression and diabetes distress. Further trials utilizing Internet and mobile technologies for the mental health of people with diabetes are currently being conducted [36], including our own study using a local iCBT study for depression in people with diabetes [37]. A recent report of an online diabetes self-management program, of the sort which could compliment depression resources reported 'small but significant' benefits as a stand-alone program [38] but points to the need for a mixture of face-to-face and online resources targeted to individual needs.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based interventions have also been used as an add-on support to in-person treatment. A recent RCT found that the addition of a web-based intervention focused on skills for achieving and maintaining abstinence resulted in an increase in abstinence compared to treatment-as usual (75). This effect was more pronounced in individuals with a positive breath alcohol at study entry (75).…”
Section: Psychosocial Treatmentmentioning
confidence: 99%
“…Four of them used homework assignments to encourage patients to apply the learned skills in daily practice [21,31,32,52]. Two added mood, thought, behavior and/or diabetes selfmanagement reporting [30,31].…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…Three addressed no logging to the web site or no homework received by e-mail (mainly standardized) or in last instant by phone call from the clinician when e-mail had no response [21,32,52]. Cohn and cols [31] intervention used payment as a motivation strategy, they paid $1 for each daily report completed, $20 for completing the final questionnaires and phone interview, and $20 if they completed the study within 75 days with reports on at least 75% of all days.…”
Section: Adherence Managementmentioning
confidence: 99%
See 1 more Smart Citation